2020
DOI: 10.3389/fneur.2020.00438
|View full text |Cite
|
Sign up to set email alerts
|

Blast Exposure Leads to Accelerated Cellular Senescence in the Rat Brain

Abstract: Blast-induced traumatic brain injury (bTBI) is one of the major causes of persistent disabilities in Service Members, and a history of bTBI has been identified as a primary risk factor for developing age-associated neurodegenerative diseases. Clinical observations of several military blast casualties have revealed a rapid age-related loss of white matter integrity in the brain. In the present study, we have tested the effect of single and tightly coupled repeated blasts on cellular senescence in the rat brain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 70 publications
(88 reference statements)
2
15
0
Order By: Relevance
“…The results of this study are consistent with recently published mouse models of mTBI in which DNA damage has been reported in the early (24 h) period [ 3 , 123 , 151 ]. Our own studies on human autopsy cases showed strong evidence of DSBs in brains of athletes with a history of rmTBI [ 131 , 132 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study are consistent with recently published mouse models of mTBI in which DNA damage has been reported in the early (24 h) period [ 3 , 123 , 151 ]. Our own studies on human autopsy cases showed strong evidence of DSBs in brains of athletes with a history of rmTBI [ 131 , 132 ].…”
Section: Discussionsupporting
confidence: 92%
“…This can lead to widespread DNA damage [ 28 ]. Indeed, accumulation of DNA damage has been reported in various models of mTBI [ 3 , 123 , 151 ] and our lab has previously shown evidence of double-strand breaks (DSBs) in human brains with mTBI history [ 131 , 132 ]. Although cells throughout the body regularly encounter DNA damage from endogenous sources, such as metabolic reactive oxygen species (ROS), the cell’s DNA damage response (DDR) can become overwhelmed when facing pathological levels of damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advanced blast simulator (ABS) described previously was used for the blast exposure ( 18 , 19 ). For blast exposure, the rats were anesthetized with 4% isoflurane for 8 min and secured in a longitudinal (i.e., rat facing the oncoming shockwave) prone orientation in the test section of the ABS.…”
Section: Methodsmentioning
confidence: 99%
“…To produce moderate injury to the auditory system, we used Valmax membranes yielding peak positive static pressures of ~19 psi with a positive phase duration of 4–5 msec. For tightly coupled repeated blast exposures, the rats were exposed to two 19-psi blast overpressure waves separated by 2 min as described earlier ( 18 , 19 ). Sham control rats received only the anesthesia and handling and were not exposed to blast.…”
Section: Methodsmentioning
confidence: 99%